Unravelling the structure and function of the petal appendages in the tribe Schwenckieae (Solanaceae). (13th December 2019) - Paucar, J. O. A.; Isaias, R. M. S.; Stehmann, J. R.
Abstract: The tribe Schwenckieae ( Solanaceae ) is characterised by the presence of appendages on the corolla, a diagnostic trait for the group. These appendages constitute a median distal projection of the three‐lobed petal and occur in the genera Melananthus and Schwenckia but are absent in Heteranthia . We investigated the micromorphology and anatomical structure of the appendages and lateral petal lobes of Schwenckia americana (two varieties), S. angustifolia, S. curviflora and S. novaveneciana, and Melananthus fasciculatus . We also performed histochemical tests to determine if the appendages are involved in the production of volatiles, acting as a fragrance secretory structure (osmophore). The appendages have a uniseriate epidermis, whose cells store phenolics and lipids. The parenchyma is starch‐rich just prior to anthesis in all species studied. The sensory test and anatomical analyses identified scent‐secreting tissues, not only in the appendages, but also in the lateral petal lobes, whose cells are papillose with a sculptured surface. The α‐naphthol p ‐phenylenediamine (NADI) reaction detected volatile (essential oils) compounds in S. americana var.  americana and S. americana var.  angustifolia. We demonstrated the secretory tissues and the production of lipids in the corolla appendages of Schwenckia and Melananthus, which indicate their osmogenic function and probable scent emission to attract pollinators. Abstract : The tribe Schwenckieae (Solanaceae) is characterized by the presence of appendages (median petal lobe) on the corolla. The anatomical structure and histochemical tests showed the osmogenic function of the appendages in Schwenckia and Melananthus, probably playing a role in scent emission and pollinator atraction.